WhatsApp como incentivo ao jornalismo participativo transformações no TN 1ª Edição, da rotina produtiva ao relacionamento com o telespectador - Garau, Elaine de Lima Castro (2018)
This dissertation looks at the usage of the WhatsApp - an app for sending and receiving instant messages - in the TV News, specifically applied at the Tribuna Notícias 1st Edition, a TV news show at the TV Tribuna, channel associated to the Brazilian Television System in Espírito Santo, Brazil. After participant´s research carried out on the field and through semi-structured interviews, it became clear that the usage of such apps lead to transformations both in the productive routines of professionals involved in the writing process and it impacted journalists and viewers relationship. The app´s usage transform communicational processes, similarly to what happens with all new technology, thus affecting directly the news´ routine, reshaping the production, sending and receiving information workflow chain. The stumbling blocks for this tool advancement usage are the imposed business limitations, essentially lack of resources, mainly overloaded personnel performing multiple functions, leading to high workload and also lack of innovation´s training and skills. This research shows that the usage of WhatsApp in the writing edition of the Tribuna Notícias, begun with journalism professionals exhilarated by the possibilities of progress, speed and more interaction with the public, however after the first few months, the exhilaration was replaced by frustration. In one side, it was observed that viewers became unhappy after responding to the stimulation to participate in a more interactive way in the news production. A part of them, was disappointed for not having their expectation´s met, neither they felt represented in the news. On the other side, there are overloaded and disappointed professionals, that believe they possess a technology capable to bring great benefits to the newsmaking and to the journalistic process end-product. They are aware that is not feasible to develop this process, in a reasonable way with the resources available at hand. The main authors´ references are Alfredo Vizeu (2000, 2004, 2005) and Beatriz Becker (2009, 2012, 2016)